On the Configuration of Supercapacitors for Maximizing Electrochemical Performance - Zhang, Jintao; Zhao, X. S. (ChemSusChem, 2012)
Supercapacitors, which are attracting rapidly growing interest from both academia and industry, are important energy‐storage devices for acquiring sustainable energy. Recent years have seen a number of significant breakthroughs in the research and development of supercapacitors. The emergence of innovative electrode materials (e.g., graphene) has clearly provided great opportunities for advancing the science in the field of electrochemical energy storage. Conversely, smart configurations of electrode materials and new designs of supercapacitor devices have, in many cases, boosted the electrochemical performance of the materials. We attempt to summarize recent research progress towards the design and configuration of electrode materials to maximize supercapacitor performance in terms of energy density, power density, and cycle stability. With a brief description of the structure, energy‐storage mechanism, and electrode configuration of supercapacitor devices, the design and configuration of symmetric supercapacitors are discussed, followed by that of asymmetric and hybrid supercapacitors. Emphasis is placed on the rational design and configuration of supercapacitor electrodes to maximize the electrochemical performance of the device. Charged and ready to go: In the past few years, significant breakthroughs in the development of supercapacitors as energy‐storage devices is promoted by the emergence of innovative electrode materials (e.g., graphene) and driven by rapidly increasing demands for high‐performance energy‐storage devices (see picture; ASC/SSC=asymmetric/symmetric supercapacitor.